Your child at play - Segal, Marilyn M. (Your child at play series, 2000)
Brand new to the successful "Your Child at Play" series (over 200,000 sold of the first four volumes), this fifth volume is the first book focusing on how play fosters the development of five- to eight-year-olds at home and at school, with more than 100 photos. Based on extensive research with parents, their children, and teachers, respectful of cultural differences, and written in a jargon-free, parent-friendly style, this generously illustrated book is packed with learning activities, games, poems, and recipes, as well as anecdotes and advice. Divided into eight chapters, readers follow a group of children through play and learning settings, see how they look at the world, and what activities they enjoy with family and friends. Each chapter ends with a "Questions and Answers" section and a collection of "Play Ideas." A unique and delightful book for parents, teachers and caregivers, "Your Child at Play: Five to Eight Years" makes an invaluable contribution to the child care/parenting field.